Morphological likeness of the skeletal remains in a Central European family from 17th to 19th century - Veleminský, P; Dobisíková, M (Homo, 2005)
In spite of a recent preferential application of molecular genetic methods to kinship determination of anonymous human skeletal remains, the classical anthropological methods cannot be rejected as they are simple, quick and give access to a large part of a genome. This paper deals with the extent of morphological skeletal similarity in persons of known genealogical relationship. The skeletal remains of eight individuals from the family tomb of the Swéerts-Sporck's noble family in castle Kuks, East Bohemia, Czech Republic were analysed. Basic personal details, as well as data on their genealogical relationship, were available. Individuals were compared according to 173 anatomical variants--epigenetic traits, 90 of which were located on the skull and 83 on the postcranial skeleton. For each trait the percentile coincidence and/or difference were calculated. We observed the highest coincidence between the father and his son. These two individuals showed both closest correlation in the presence and the least difference in the occurrence of anatomical variants, as well as a high value of paternal probability. Clear kinship was also detected among cousins of the same or opposite sex. However, kinship between brother and sister was not so evident. The greatest difference was observed amongst biologically unrelated family members such as women who married into the family. The individuals under investigation showed a significantly higher occurrence of three among four traits of the sella turcica (ponticulus carotico-clinoideus, ponticulus interclinoideus, taenia interclinoidea; 99% confidence). A significantly higher occurrence of the ponticuli basales ossis sphenoidalis, palatine torus and the costal articular surface on the body of 7th cervical vertebrae was also found (95% confidence). Our results, therefore, suggest that these morphological variants might be considered as family-specific traits.
Keywords: Female; pohřeb; rodina; Social Class; Pedigree; ženské pohlaví; rodokmen; History, 18th Century; kosti a kostní tkáň; lidé; Anthropology, Physical; Male; Czech Republic; Burial; History, 19th Century; dějiny 18. století; společenská třída; Family; Česká republika; antropologie fyzická; History, 17th Century; mužské pohlaví; dějiny 19. století; dějiny 17. století; Bone and Bones; Humans